2004
DOI: 10.2355/isijinternational.44.1738
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of the Fe-Al-C Ternary System by Incorporating ab initio Energetic Calculations into the CALPHAD Approach

Abstract: A thermodynamic analysis of the Fe-C-Al ternary system has been carried out covering a wide range of temperatures and composition. Special care was taken to the expression of the free energy for the ternary Perovskite carbide phase, Fe 3 AlC (k), by considering the crystallographic similarity between the k phase and the L1 2 structure. The free energy was calculated using the (Fe,Al) 3 (Fe,Al) 1 (C,Va) 1 sublattice model, and the k and L1 2 structures were treated as a continuous solution. Because of the lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 11 publications
3
21
1
Order By: Relevance
“…The only published value to which this is comparable was calculated recently by Ohtani. [9] The authors used the FLAPW method in the GGA approximation with the WIEN2k package. They report À27.9 kJ/mol.…”
Section: The Ternary K-fe 3 Alc Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…The only published value to which this is comparable was calculated recently by Ohtani. [9] The authors used the FLAPW method in the GGA approximation with the WIEN2k package. They report À27.9 kJ/mol.…”
Section: The Ternary K-fe 3 Alc Compoundmentioning
confidence: 99%
“…The perovskite k-Fe 3 AlC carbide, in particular, is hardly known. Partial information has been published: Palm and Inden have investigated experimentally specific Gibbs isotherms of the Fe-Al-C system, [8] and recently, Ohtani et al [9] published a Fe-Al-Ni-C phase diagram based on ab initio calculations.…”
Section: Introductionmentioning
confidence: 98%
“…Experimental studies on phase equilibria have been, thus, carried 45 out for the Fe-Al-C [33] and Fe-Mn-Al-C [34] systems. Furthermore, CALPHAD type thermodynamic calculations have been extensively performed in materials science to critically assess the phase relations under arbitrary thermodynamic conditions, for instance investigation of the Fe-Al-C system has been done by Ohtani et al [35] and Connetable et al [48] where the ordered κ-carbide in the Fe-Al-C ternary sys-50 tem was calculated by applying formalisms that allow intermixing between Fe and Al, and non-stoichiometry in the carbon content. However, a narrow range of Al content were calculated in both studies.…”
Section: Modelmentioning
confidence: 99%
“…The phase composition of this alloy as given in the phase diagram [7] (see Fig. 2) is iron aluminide FeAl plus aluminium carbide Al 4 C 3 , which was identified by X-ray diffraction.…”
Section: Resultsmentioning
confidence: 99%
“…These authors identified two-phase material α-FeAl + C (graphite). By contrast, Ohtani et al [7] found using CALPHAD a mixture of α-FeAl + Al 4 C 3 under the same conditions. Recently also the Fe 3 Al-type aluminides were used to be hardened by carbon (~ 4-5 at.…”
Section: Introductionmentioning
confidence: 85%